Badminton preferentially decreases explosive over maximal voluntary torque in both the plantar flexors and extensors - Girard, O.; Behan, F. P.; Cabello-Manrique, D.; Fernandez-Fernandez, J. (Translational Sports Medicine, 2019)
We assessed changes in maximal and explosive plantar flexion (PF) and dorsi flexion (DF) torque, and thus the maximal and explosive DF/PF ratio, in response to successive badminton matches (2 × 35, 15 minutes of rest) in 16 juniors (10 males, 6 females) International-level badminton players before (Pre), immediately after the first (Post-1) and second (Post-2) match as well as after resting for 12 hours. For both PF and DF, maximal voluntary torque decreased from Pre to Post-2 (~7%-9%; P < 0.05). Compared with Pre, PF explosive voluntary torque decreased by ~4%-13% at Post-1 (P < 0.05), with further reductions ranging from -15% to -25% within the 0-100 ms epoch after contraction (P < 0.001) at Post-2. Decrements of similar magnitude in DF explosive voluntary torque occurred at Post-1 (ranging -7% to -27%) and Post-2 (ranging -3% to -28%) relative to Pre (P < 0.05). All neuromuscular parameters were fully recovered after 12 hours of rest. Explosive DF/PF ratios during the very initial phase of contraction (up to 50 ms from onset) were lower compared with the maximal DF/PF ratio, with no effect of time (all P < 0.05). In badminton, explosive torque indices should be included to more accurately reflect acute fatigue induced by successive badminton matches.